A Phytophthora capsici RXLR effector targets and inhibits the central immune kinases to suppress plant immunity. Issue 1 (22nd July 2021) - Liang, Xiangxiu; Bao, Yazhou; Zhang, Meixiang; Du, Dandan; Rao, Shaofei; Li, Yixin; Wang, Xiaodan; Xu, Guangyuan; Zhou, Zhaoyang; Shen, Danyu; Chang, Qin; Duan, Weiwei; et al.
Summary: Receptor‐like cytoplasmic kinase subfamily VII (RLCK‐VII) proteins are the central immune kinases in plant pattern‐recognition receptor (PRR) complexes, and they orchestrate a complex array of defense responses against bacterial and fungal pathogens. However, the role of RLCK‐VII in plant–oomycete pathogen interactions has not been established. Phytophthora capsici is a notorious oomycete pathogen that infects many agriculturally important vegetables. Here, we report the identification of RXLR25, an RXLR effector that is required for the virulence of P .  capsici . In planta expression of RXLR25 significantly enhanced plants' susceptibility to Phytophthora pathogens. Microbial pattern‐induced immune activation in Arabidopsis was severely impaired by RXLR25. We further showed that RXLR25 interacts with RLCK‐VII proteins. Using nine rlck‐vii high‐order mutants, we observed that RLCK‐VII‐6 and RLCK‐VII‐8 members are required for resistance to P. capsici . The RLCK‐VII‐6 members are specifically required for Phytophthora culture filtrate (CF)‐induced immune responses. RXLR25 directly targets RLCK‐VII proteins such as BIK1, PBL8, and PBL17 and inhibits pattern‐induced phosphorylation of RLCK‐VIIs to suppress downstream immune responses. This study identified a key virulence factor for P. capsici, and the results revealed the importance of RLCK‐VII proteins in plant–oomycete interactions.